Analysis of Vinylene Carbonate (VC) as Additive in Graphite/LiNi0.5Mn1.5O4 Cells. Issue 12 (31st August 2017) - Pritzl, Daniel; Solchenbach, Sophie; Wetjen, Morten; Gasteiger, Hubert A.
Abstract : Vinylene Carbonate (VC) is an effective electrolyte additive to produce a stable solid electrolyte interphase (SEI) on graphite anodes, increasing the capacity retention of lithium-ion cells. However, in combination with LiNi0.5 Mn1.5 O4 (LNMO) cathodes, VC drastically decreases cell performance. In this study we use on-line electrochemical mass spectrometry (OEMS) and electrochemical impedance spectroscopy (EIS) with a micro-reference electrode to understand the oxidative (in-)stability of VC and its effect on the interfacial resistances of both anode and cathode. We herein compare different VC concentrations corresponding to VC to graphite surface area ratios typically used in commercial-scale cells. At low VC concentrations (0.09 wt%, corresponding to 1 wt% in commercial-scale cells), an impedance increase exclusively on the anode and an improved capacity retention is observed, whereas higher VC concentrations (0.17 wt – 2 wt%, corresponding to 2 wt - 23 wt% in commercial-scale cells) show an increase in both cathode and anode impedance as well as worse cycling performance and overcharge capacity during the first cycle. By considering the onset potentials for VC reduction and oxidation in graphite/LNMO cells, we demonstrate that low amounts of VC can be reduced before VC oxidation occurs, which is sufficient to effectively passivate the graphite anode.